A layered unity model of split-brain consciousness. - Lopez, Azenet (Philosophical Studies, 2025)
Split-brain subjects can consciously perceive and identify two stimuli presented simultaneously but separately in opposite hemifields. Yet, they seem to lack a conscious experience of the two stimuli together, as they cannot judge whether these are the same or different. Such breakdowns in experiential or phenomenal unity would carry important implications for philosophical reflection on the essential properties of conscious experience, as well as for scientific theorising about consciousness' neural and functional bases. Extant models supporting the preserved unity of split-brain consciousness secure unity in a subject or agential sense, but do not explain how right- and left-side conscious experiences could be unified in the problem cases. Here, I offer a new model that supplies the missing phenomenal unity. Based on the construct of layers of conscious experience, my model acknowledges breakdowns in local experiential layers but warrants preserved unity in global ones. A supporting argument draws on the preserved attentional capacities of split-brain subjects. My proposal goes beyond extant research in that it focuses on the conjoint phenomenology of simultaneous right- and left-side experiences, highlights the conceptual connections of phenomenal unity to attention, and discusses the impact of specific split-brain attentional capacities on the unity of right- and left-side experiences.